Application of Biochar-Immobilized Bacillus megaterium for Enhancing Phosphorus Uptake and Growth in Rice - Keru Yu; Zhenyu Wang; Wenyan Yang; Shuai Li; Dongtao Wu; Hongtao Zheng; Zhengqian Ye; Shaona Yang; Dan Liu (Plants)
Phosphorus (P) is an essential nutrient for rice growth, and the presence of phosphate-solubilizing bacteria (PSB) is an effective means to increase soil P content. However, the direct application of PSB may have minimal significance due to their low survival in soil. Biochar serves as a carrier that enhances microbial survival, and its porous structure and surface characteristics ensure the adsorption of Bacillus megaterium. Inoculating rice husk biochar-immobilized with Bacillus megaterium (BMB) resulted in dissolved inorganic and organic P levels of 39.55 and 31.97 mL L−1, respectively. Subsequently, rice pot experiments were conducted to investigate the response of soil microbial P mobilization and P uptake in rice to fertilizer inputs. The organic fertilizer (OF) combined with BMB treatment (MOF) showed the highest soil available phosphorus (AP) at 38 days, with a value of 7.83 mg kg−1, as well as increased the pqqC abundance while decreasing the abundance of phoD bacterial communities compared with the control. Furthermore, the bioavailable P reservoir (H2O–Pi and NaHCO3–Pi) in soil was greatly increased through the fertilizer input and microbial turnover, with the highest H2O–Pi (3.66 mg kg−1) in OF treatment and the highest NaHCO3–Pi (52.65 mg kg−1) in MOF treatment. Additionally, carbon utilization analysis was applied using the commercial Biolog system, revealing that the MOF treatment significantly increased the utilization of carbohydrates, polymers, and amino acid carbon sources. Moreover, compared to the control, MOF treatment significantly increased the shoot (0.469%) and root P (0.516%) content while promoting root development and thereby supporting rice growth. Our study demonstrates that the MOF treatment displayed higher P levels in both soil and rice plants, providing a theoretical basis for further understanding the role of biochar-based bacterial agents in rice P management.